Puteri Gunung Ledang in popular media: womanhood, femininity and gender in Puteri Gunung Ledang (2004) and Magika (2010) - Hassan, Nurul Izzati; Ramlan, Wan Nur Madiha (Dewan Bahasa dan Pustaka, 2023)
This paper examines two recent films about the legend of Puteri Gunung Ledang in order to analyse what they might tell us about contemporary representations of the mythical figure. In doing so, it will focus on how evolving ideas of womanhood, femininity, and gender portray how Puteri Gunung Ledang is represented in contemporary media. Stories of Puteri Gunung Ledang in 21st century films will be studied using a poststructuralist feminist approach, which is guided primarily by Julie Sanders' theory of Adaptation and Appropriation. Puteri Gunung Ledang is one of the most popular tales in Malay culture and is included in Sulalatus Salatin, a text that highlights some of the most important historical events during the Malacca Sultanate. Today, Puteri Gunung Ledang has been rewritten for children and young adult fiction and adapted into other media, such as films and plays. However, the portrayal and characterization of the titular character have evolved, not just in printed versions of the story but also in other popular cultural forms, such as film.